Implementasi Total Quality Management (TQM) dalam Manajemen Perpustakaan di Dinas Perpustakaan dan Kearsipan Musi Banyuasin - Rozali Kholid (Perpustakaan Nasional RI, 2022)
This thesis discusses the Implementation of Total Quality Management (TQM) in Library Management at the Musi Banyuasin Library and Archives Service. This study aims to find out what the implementation strategy is, to know the inhibiting and supporting factors, and know the steps of the library in improving the quality of services at the Musi Banyuasin Library and Archives Service. The type of research used is qualitative data, which means that the data is in the form of an explanation of matters relating to the implemetation of Total Quality Management (TQM) in Library management at the Musi Banyuasin Library and Archives Service. Methods of data collection in this study in the form of observation, interviews, and documentation. The informants in this study were the head of the library, the head of the sub-divison for processing materials and library data and reporting, and five library users from Musi Banyuasn. The results of this study indicate the implementation strategy of Total Quality Management (TQM) at the Musi Banyuasin Library and Archives Service by apllying the principles of Hensler and Brunell theory consisting of customer satisfaction (users), respect for everyone, management based on facts, and improvement. Continuous. Meanwhile, efforts to improve service quality are based on the theory of Goetsch and Davis, which consist of a focus on customers, libraries to improve service quality, long-termcommitment, teamwork, education and training, freedom of control. The inhibiting and supporting factors, include funds, goverment support, training and promotion programs.